(untitled) (Journal of Pharmaceutical Negative Results, 2023)
INTRODUCTION: Ovaries are a pair of organs in the female pelvis situated on both sides of the uterus, which is suspended in the pelvic cavity by the meso-ovarium and attached to the broad ligament. Ovarian neoplasms are one of the major causes of mortality and morbidity in the pelvic cavity. MATERIALS & METHODS: This situdy includes retrospective and prospective data from agust 2012 to July 2015. The surgical specimens of oophorectomy, cystectomy and totoal abdominal hyetrectomy with unilateral & bilateral salphingo-oophorectomy were included. RESULTS: 90 cases of ovarian tumours were reported during the study period. Most common were benign tumours (85.6%), followed by malignant tumours(11.11%) and borderline tumours(3.33%). The tumours arsing from epithelium were the commonest (76.7%), followed by germ cell tumour (17.8%) and sex cord stromal tumours (5.6%). Benign tumours were common than malignant tumours. As the age advances the malignant tumours were common. Most of the tumours were unilateral, only minor proportion were bilateral. CONCLUSION: The Histomorphogical diagnosis of ovarian neoplasms categorises the tumours into benign, borderline and malignant. Benign variant is more common than malignant tumours especially the surface epithelial tumour are the commonest followed by germ cell tumours and sex cord stromal tumours.